2013
DOI: 10.1007/s00005-013-0266-6
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Cholinergic Signaling in Adipose Tissue and Pancreatic Islets Biology: Revisited Function and Therapeutic Perspectives

Abstract: Nicotinic acetylcholine receptors (nAChRs) are membrane ligand-gated cation channels whose activation is triggered by the binding of the endogenous neurotransmitter acetylcholine or other biologic compounds including nicotine. Their roles in synaptic transmission in the central and peripheral nervous system as well as in the neuromuscular junction have been extensively studied. Recent implications of nAChRs in intracellular signaling and their detection in peripheral nonneural cells (including epithelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 155 publications
0
13
0
Order By: Relevance
“…Nicotine is an alkaloid naturally produced by the tobacco plant that binds nicotinic acetylcholine receptors, found throughout neuronal and non-neuronal or visceral organs. These receptors participate in signaling within the central and peripheral nervous system and in a number of metabolic tissues, including pancreatic islets, adipose tissue, macrophages, liver, and skeletal muscle [1417]. Nicotine has been shown to directly alter glucose homeostasis [18], suggesting an important role for this additive in the development of T2D.…”
Section: Smoking Leads To a Variety Of Chemical Exposuresmentioning
confidence: 99%
“…Nicotine is an alkaloid naturally produced by the tobacco plant that binds nicotinic acetylcholine receptors, found throughout neuronal and non-neuronal or visceral organs. These receptors participate in signaling within the central and peripheral nervous system and in a number of metabolic tissues, including pancreatic islets, adipose tissue, macrophages, liver, and skeletal muscle [1417]. Nicotine has been shown to directly alter glucose homeostasis [18], suggesting an important role for this additive in the development of T2D.…”
Section: Smoking Leads To a Variety Of Chemical Exposuresmentioning
confidence: 99%
“…nAChRs are found in the neuromuscular junction, and in peripheral and central nervous systems throughout the animal kingdom, and play important roles in regulating synaptic transmission (3)(4)(5)(6)(7)(8)(9). Neuronal nAChRs are pentameric membrane-bound proteins, which are made up of ␣ (␣2-␣10) and ␤ (␤2-␤4) subunits (10).…”
mentioning
confidence: 99%
“…We also preliminarily confirmed the expression of the α2, α5 and β2 subunits, as well as the α7 subunit (Figure ; Table ). The α7 subunit is the most common subunit in the previous islet studies, and its specific agonist has recently been shown to have a protective effect against cytokine‐induced β‐cell apoptosis and eventual diabetes in vivo . On the basis of these findings, we investigated the α7 subunit‐specific effect on T‐UPR and apoptosis under ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent reports emphasize the importance of nAChR signaling by showing that although cholinergic innervation of human islets is limited, ‐cells can substitute to secrete ACh to stimulate surrounding endocrine cells in a paracrine manner. Supporting an important role of nAChR signaling in glucose metabolism, in vivo , it was reported that nicotine ameliorates the diabetic phenotype in db / db mice, Zucker fatty rats, streptozotocin‐induced diabetic mice and even NOD mice. Furthermore, stimulation of nAChR by nicotine increases insulin secretion in rodent β‐cells, and decreases cytokine‐induced apoptosis in human and rodent islets at least through the α7 nAChR subunit.…”
Section: Introductionmentioning
confidence: 99%